New Values of Cultural Heritage and the Need for a New Paradigm Regarding its Care - Iwona Szmelter (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The concept of cultural heritage values is a living idea. Currently, “cultural heritage” is a broader term, which includes natural and man-made legacy. Conservation and diverse museum activities have a fundamental practical side, which must be realised in conjunction with theoretical constructs. The complex care of cultural heritage in the field of visual arts involves a set of new values, stories, ideas, traditions, symbols, attitudes, and accomplishments. The new role of the conservator-restorer acting as an “advocate” of the intrinsic values and well-being of a given object in tangible and/or intangible heritage is affirmed as that of an “orchestrator” of conservation process. Valuation plays a crucial role in recognition, strategic decision-making, and in complex negotiations devoted to the care of cultural heritage, which can often be very difficult in theory and also in conservation practice.  We now understand that the protection and management of cultural heritage resources are a way of ensuring their maximum possible vitality, values and functions to the benefit of current and future generations, attributing them an important role in a sustainable social system.